Health care practices performed by agriculturists during the puerperal period - Nivea Shayane Costa Vargas; Teila Ceolin; Sidnéia Tessmer Casarin; Marjoriê da Costa Mendieta; Caroline Vasconcellos Lopes; Manuelle Arias Piriz (Universidade Federal de Santa Maria, 2017)
Aim: to know the practices of health care carried out in the puerperal period by families of farmers in a city in the south of the state of Rio Grande do Sul. Method: a qualitative study, carried out in a rural area of a municipality in the southern region of Rio Grande do Sul. Data collection occurred from May to September 2014, through semistructured interviews, which were recorded. The data were analyzed according to Minayo's operational proposal. Results: twenty-five participants who practice family farming were approached. Cultural legacy still influences the health care provided to puerperal women and their newborns. The most cited care practice that were performed during the puerperal period were related to food intake, breastfeeding, hygiene, and work. Final Considerations: it is important that the nurses give proper attention to the main cultural care carried out by the families, seeking to comprehend them, in order to achieve integral health care